Anormalidad de Pseudo Chediak-Higashi en un caso de Leucemia Mieloide Aguda, observado en sangre periférica (2013)
ABSTRACT: Pseudo Chediak Higschi granules have been reported in myeloid neoplasms, especially in acute myeloid leukemias with maturation and with translocation t(8;21)(q22;q22) (RUNX1T1). These granules are different to Auer bodies and they correspond to fine, larger and irregular intra-cytoplasmic structures. Herein, hematological findings of a patient with diagnosis of acute myeloid leukemia are presented, in accordance with World Health Organization criteria. In the peripheral blood smear, unique or multiple Pseudo Chediak Higashi granules with a pink color and crystalloid aspect were observed, especially in blast cells and neutrophilic myelocites.